Capitalism and the Legal Foundations of Global Reparations - Franklin Obeng-Odoom (Journal of Law and Political Economy, 2023)
It is widely contended that Africans were complicit in enslaving other African people, that slavery was legal at the time it was in force and, hence, that demanding reparations from states can have no legal basis. Drawing on the work of Nora Wittmann, this essay questions these presumptions, advances the argument that there is a legal basis for reparations, and puts the case for grounding the legal approach within a wider political economy of reparations.